Composition Effect on the Pore Structure of Transitional Shale: A Case Study of the Permian Shanxi Formation in the Daning–Jixian Block at the Eastern Margin of the Ordos Basin - Zhang, Qin; Qiu, Zhen; Zhao, Qun; Zhang, Leifu; Dong, Dazhong; Wang, Yuman; Hou, Wei; Li, Shuxin; Li, Xingtao (Frontiers in Earth Science, 2022)
Marine–continental transitional (hereinafter referred to as transitional) Permian shales are the important targets for shale gas in China for its significant volumes of shale gas resources. However, the influence of its mineral composition on pore structure remains unclear. In this study, Shale samples from the Permian Shanxi Formation in the Daning–Jixian Block at the eastern margin of the Ordos Basin were collected to investigate the effects of organic and inorganic compositions on the development of pore structures through organic petrographic analysis, X–ray diffraction (XRD), scanning electron microscope (SEM) observation, gas adsorption, high pressure mercury injection (HPMI) and methane adsorption experiments. The organic petrographic analysis reveals that Shanxi shale is composed of type II2–III kerogens, and the average vitrinite reflectance (Ro) is 2.3% at the over–mature stage or dry gas window. Shale interval at the bottom of the lagoon facies is considered as the most favorable interval throughout the entire section because of its high TOC content (4.19%–43.9%, average of 16.9%) and high brittle mineral content (38.3%–73.2%,average of 55.8%). Gas (N2 and CO2) adsorption and HPMI tests reveal the pore size distribution characteristics of the shale. The full pore size distribution reveals that micropores and mesopores are dominant in the pore system, and the contribution of the two kinds of pores are equivalent, accounting for 21.95%–55.05% (average of 42.3%) and 37.94%–64.6% (average of 49.64%). By using content differentiation method, the pore size distribution of OM and clay minerals were quantitatively analyzed. OM contains numerous SEM-invisible micropores, whereas clay minerals mainly develop mesopores and small–sized macropores. The OM contribution to the surface area and pore volume accounts for 73.2% and 33.5%, respectively. For thermally over–mature transitional shales, both OM and clay minerals are important for the storage capacity of absorbed and free gas.